Arahan Alokasi Pengembangan Komoditas Unggulan di Kabupaten Muna Sulawesi Tenggara - Yusman Syahrir Ando; Abdul Rachman Rasyid; Muhammad Fathien Azmy (Jurnal Wilayah & Kota Maritim (Journal of Regional and Maritime City Studies), 2020)
Muna Regency, Southeast Sulawesi is an area that has the potential for climate and land conditions with various characteristics. The diversity of the physical properties of the land can be used as a basis for consideration in determining commodity areas. The agricultural sector with food crops and plantation sub-sectors is the largest contributor to the growth of Gross Regional Domestic Product (GRDP) in the Muna Regency area. The aim of this research is to determine the leading commodity, analyze the land suitability of the leading commodity, and provide direction for the location of the development of the leading commodity. This research was conducted from February to July 2020 (5 months). This research is a quantitative and qualitative research using secondary data collected through literature studies and primary data collected by observation and documentation. The analysis used is Location Quotient (LQ), shift-share, and spatial analysis. The results of the study indicate that the leading commodity in Muna Regency is soybeans with an appropriate land class level (S1), which is 26,894.38 ha and a fairly suitable land class (S2), which is 135,809.41 ha. Directions for the location of the superior commodity of soybeans are based on a priority scale, namely priority I with an appropriate land classification of 3,851.18 ha and priority II with a fairly appropriate land classification of 11,001.75 ha.